Sejarah Perkembangan Madrasah di Indonesia - Supani Supani (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Madrasah term in Indonesia nowadays known as religious education institute. Some people sometimes mistaken when understanding the meaning of madrasah because didn’t understand about chronological development of madrasah itself. Therefore, emerge dichotomy between madrasah (religious education) with secular education. Some people presume that learning at madrasah only to master other-world (akhirat) science, whereas learning at secular education mean to master worldly matter. This dichotomy if let prolonged will trigger conflict. Actually there’s long history that make madrasah still exist until now as education institution. From this argument, this article will describe history of madrasah in Indonesia and its development.